Making the "American Acropolis": On Verticality, Social Hierarchy, and the Obduracy of Manhattan Schist. Issue 1 (2nd January 2020) - Gregory, Steven
Abstract : This article examines the development of the American Acropolis, a constellation of religious, cultural, and educational institutions in Morningside Heights, New York City. I argue that, beginning in the 1880s, the elites governing these institutions took advantage of geography—specifically, the area's elevation as a plateau—and their control over the built environment to achieve vertical secession, physically and symbolically, from nearby working-class communities and their associated industries. Over the longue durée, these elites viewed social secession to be conducive to, if not the necessary condition for, cultivating the arts of civilization. I examine the ensuing politics of verticality that accompanied this secession, pitting the institutions of the Acropolis against sectors of the real estate industry, railroad companies, and the ethnically and racially marked populations of neighboring working-class communities. Key Words: American Acropolis, materiality, Morningside Heights, politics of verticality, social hierarchy, social secession.